An ImmunoFET Coupled with an Immunomagnetic Preconcentration Technique for the Sensitive EIS Detection of HF Biomarkers - Ben Halima, Hamdi; Zine, Nadia; Nemeir, Imad Abrao; Pfeiffer, Norman; Heuberger, Albert; Bausells, Joan; Elaissari, Abdelhamid; Jaffrezic-Renault, Nicole; Errachid, Abdelhamid (Micromachines, 2024)
We propose a new strategy using a sandwich approach for the detection of two HF biomarkers: tumor necrosis factor-α (TNF-α) and interleukin-10 (IL-10). For this purpose, magnetic nanoparticles (MNPs) (MNPs@aminodextran) were biofunctionalized with monoclonal antibodies (mAbs) using bis (sulfosuccinimidyl) suberate (BS3) as a cross-linker for the pre-concentration of two biomarkers (TNF-α and IL-10). In addition, our ISFETs were biofunctionalized with polyclonal antibodies (pAbs) (TNF-α and IL-10). The biorecognition between pAbs immobilized on the ISFET and the pre-concentrate antigen (Ag) on MNPs was monitored using electrochemical impedance spectroscopy (EIS). Our developed ImmunoFET showed a low detection limit (0.03 pg/mL) toward our target analyte when compared to previously published electrochemical immunosensors. It showed a higher sensitivity than for other HF biomarkers. Finally, the standard addition method was used to determine the unknown concentration in artificial saliva. The results matched with the expected values well.
CRIS-Team Scopus Importer:2024-04-19
Keywords: electrochemical impedance spectroscopy; heart failure; interleukin-10; saliva analysis; tumor necrosis factor-α